Cardiac metastasis of lung cancer presented as mimicking ST-elevation myocardial infarction with reciprocal electrocardiographic changes. Issue 3 (September 2022) - Kunishige, Ryuichi; Matsuoka, Yujiro; Yoshimura, Ryutaro; Fujii, Yoshitaka; Fujimoto, Kohei; Nishida, Tatsuya; Wakasa, Kenichi; Horio, Takeshi
Abstract: We report the case of a patient with metastatic cardiac tumor who presented with chest pain and electrocardiographic changes mimicking acute inferior myocardial infarction. An 84-year-old man who had undergone lung cancer surgery one year earlier was referred to emergency outpatient visit because of chest pain. His 12-lead electrocardiography (ECG) showed ST-segment elevation in the inferior leads with reciprocal ST-segment depression in the precordial and lateral leads, which was initially interpreted as inferior acute myocardial infarction. By emergency coronary angiography, however, there was no significant stenosis or occlusion in the right coronary artery or the left circumflex artery. In echocardiographic examinations after admission, a large mass was found in the area corresponding to the infero-posterior wall of the left ventricle, which had been detected only by positron emission tomography with computed tomography six months earlier. He died one month after admission. Pathological autopsy revealed a tumor of 8 × 5 cm size in the myocardium of the posterior to inferior wall of the left ventricle, and diagnosed as cardiac metastasis from lung cancer. ECG changes with ST-segment elevation, in particular persistent ST-elevation in the absence of Q waves, can be a sign for tumor invasion of the heart. Learning objective: It is necessary to consider the possibility of myocardial metastasis when a patient with malignancy presents with acute myocardial infarction-like electrocardiography findings. Besides, in this case, positron emission tomography with computed tomography (PET-CT) had detected an abnormal accumulation in the left ventricle earlier than when the tumor was pointed out by echocardiography. Multimodality imaging including PET-CT could help physicians to make the early and accurate diagnosis of metastatic cardiac tumor.